Optimalisasi Pengawetan Kurma Tomat Menjadi Serbuk Ekstrak Minuman Guna Meningkatkan Daya Simpan Pangan Nabati - Ahmad Mansur; Rudi Prasetyo Ardi; Nina Mistriani (Fakultas MIPA UNM, 2022)
Abstract. This research was conducted with a quantitative approach and aims to determine which tomato dates will be used as a basic ingredient in the manufacture of extract drinks. The use of this tomato analyzes the tolerance level of tomatoes to exposure to sugar derivatives (glucose and lactose) on shelf life as processed vegetable foods. Analyzing the antioxidant levels of tomato date extract based on storage time. Analyzing the effect of storage time on the organoleptic quality of tomato date extract. Analyzing the tolerance level of tomato date extract to exposure to sugar derivatives (glucose and lactose) and their impact on organoleptic quality. The results showed that the comparison of tomato date extract powder with various treatments had an effect on the parameters tested, including increasing antioxidants and reducing microbial levels and was also favored by research respondents when organoleptic testing was carried out. It can be concluded that the storage time of tomato date extract powder will increase antioxidant levels and will make the total microbial activity relatively decreased.Keywords: Dates Preservation, Beverage Extract, Shelf Life, Vegetable Food.